2014
DOI: 10.3389/fpls.2014.00605
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of salt tolerance in habanero pepper plants (Capsicum chinense Jacq.): Proline accumulation, ions dynamics and sodium root-shoot partition and compartmentation

Abstract: Despite its economic relevance, little is known about salt tolerance mechanisms in pepper plants. To address this question, we compared differences in responses to NaCl in two Capsicum chinense varieties: Rex (tolerant) and Chichen-Itza (sensitive). Under salt stress (150 mM NaCl over 7 days) roots of Rex variety accumulated 50 times more compatible solutes such as proline compared to Chichen-Itza. Mineral analysis indicated that Na+ is restricted to roots by preventing its transport to leaves. Fluorescence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 88 publications
(157 reference statements)
4
52
0
3
Order By: Relevance
“…The main effect when plants start becoming stressed is the reduced water content in their tissue, and therefore the closure of leaf stomatal complexes takes place. Consequently, transpiration (Bray et al, 2000) and/or photosynthesis may decrease through reduced osmotic potential in the soil solution, which involves reduced water potential (Bojórquez-Quintal et al, 2014;Penella et al, 2014aPenella et al, , 2015Penella et al, , 2016. If salinity stress occurs, a specific ionic effect appears, mediated by the accumulation of toxic ions in cellular tissues (De Pascale et al, 2003) with imbalances between nutrients (Hasanuzzaman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The main effect when plants start becoming stressed is the reduced water content in their tissue, and therefore the closure of leaf stomatal complexes takes place. Consequently, transpiration (Bray et al, 2000) and/or photosynthesis may decrease through reduced osmotic potential in the soil solution, which involves reduced water potential (Bojórquez-Quintal et al, 2014;Penella et al, 2014aPenella et al, , 2015Penella et al, , 2016. If salinity stress occurs, a specific ionic effect appears, mediated by the accumulation of toxic ions in cellular tissues (De Pascale et al, 2003) with imbalances between nutrients (Hasanuzzaman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As the underlying reason, the difference of salt tolerance among plant varieties originates from the adjustment of root Na ? uptake (Bojorquez-Quintal et al 2014;Maathuis et al 2014). After the exploitation of non-invasive micro-test technique (NMT), ion flux at root interface has been paid more attention.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the percentage of salt in the medium tested by the latter authors may have been insufficient to cause damage to the seedlings and concluded that further tests at higher concentrations should be done. Bojórquez-Quintal et al (2014) found differences between Chichen-Itza and Rex varieties belonging to the C. chinense species at different NaCl concentrations, the latter being more tolerant at the 100mM dose. However, the 150mM dose affected both cultivars, causing loss of fresh matter, foliar abscission and root darkening.…”
Section: Resultsmentioning
confidence: 85%
“…Bojórquez-Quintal et al (2014) reported that despite the economic importance of pepper, little is known about the mechanisms of tolerance to high salt concentrations.…”
Section: Introdutionmentioning
confidence: 99%